Electric vehicles based electric power grid support: a review - Afaf Rabie; Abdelhady Ghanem; Sahar S. Kaddah; Magdi M. El-Saadawi (Institute of Advanced Engineering and Science, 2023)
Grid connected electric vehicles (EVs) can provide energy quality services to ease intermittent renewable energy sources dependent, enhance grid stability performance, reliability and load balancing in the power system. Moreover, incorporating sufficient EVs into the power grid will assist reduce greenhouse gases. However, the unrestrained EVs charging impact the raise of peak request, frequency deflection, voltage instability, power quality from the acceptable limits. It can also cause overloading of the power system equipment and an increase in power losses. In this paper, the influences EV technologies on various energy systems, control scheme strategy, benefits, and motivational challenges are investigated. An overview of the impacts of uncontrolled EV loading on the electric power system and how controlled charging becomes benefit impacts is presented. Moreover, a review of the controlled charge and discharge benefits of EVs and the electrical serving involved in reduction of frequency deviation, voltage stability, power quality improvement is introduced. This review shows that integration of optimal control of EVs with a suitable optimization technique can improve and provide on time multi ancillary services of EV integrated with weak grid. In addition, this review provides research tracks which can be followed by researchers.